INTERAKSI SOSIAL ETNIS TIONGHOA DAN ETNIS MELAYU DI KELURAHAN SUNGAI BULAN SINGKAWANG UTARA - Hartini, Sri; Buwono, Sri; Wiyono, Hadi; Aminuyati, Aminuyati; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2022)
This study aims to determine social interactions in cooperation and accommodation between Chinese and Malay ethnic groups in Sungai Bulan Village, Singkawang Utara. The method used in this study is descriptive-qualitative with data sourced from the community (primary data) and documentation (secondary information). This study's informants were six people from Chinese and Malay ethnic groups in Sungai Bulan Village, Singkawang Utara. The data collection techniques used are observation, interviews, and documentation. Data reduction, data display, and conclusion drawing are the data analysis techniques used. The validity of the research data was tested using extended observations and triangulation. The results of this study show that there is cooperation in the form of association, bargaining, and collaboration. In addition, there are also accommodations in the form of compromise, mediation, and tolerance between both ethnic groups. Based on the results, social interaction in the form of cooperation and capacity between Chinese and Malay ethnic groups in Sungai Bulan Village, Singkawang Utara, is going very well.